Strategi Pengembangan Selfie Tourism Berbasis Community Based Tourism Di Goa Pandawa Dusun Brau Desa Gunung Sari Kec. Bumi Aji Kota Batu - Rodiyah, Nurul; Zurinani, Siti; Prastyo, Dikau Tondo; Arifky, Muhammad Yogi (Jurnal Ilmiah Pariwisata, 2018)
The purpose of this paper is to identify external and internal factors that can support or threaten the development of the tourist destination in Goa Pandawa and to decide the strategy of tourism development in Goa Pandawa as selfie tourism recommended. Primary data excavated is attractions, access, facilities, human resources manager, ticket prices, and promotions. In supporting the primary data, it is done by documentation. The research method used is descriptive quantitative. Primary data is obtained through observation, interviews, surveys by distributing questionnaires to Brau Village and tourists. Secondary data is obtained through focus group discussions with stakeholders. Data analysis uses Potential Analysis of Attraction Object (ODTW) and SWOT analysis (Strength, Weakness, Opportunities, and Threats). The results show that the potential of selfie tourism in Goa Pandawa is in the interval class 401-500. It means that the potential of selfie tourism is worthy to be developed because of the market potential supporting and the existence of something to see and buy. Strategies for Goa Pandawa attraction include in the strategy Rapid Growth Strategy. It means that it can optimize the rate of increase tourist visits in a faster time. By improving the quality of attractions and accessibility, it is expected that visits in the second year will be more than in the first year. Based on SWOT analysis, selfie tourism development strategy in Goa Pandawa is in quadrant 1 (aggressive).